Las fiestas cívico-electorales en San José y el reconocimiento de la autoridad de los elegidos (1821-1870) - Silva, Margarita (1993)
The author analyzes the civic/electoral festivities in San José from 1821 to 1870, and their connections with processes by which individuals in power legitimized their authority. The invention of civic/electoral rituals is thus made transparent.